2011
DOI: 10.1021/pr2009803
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic and Transcriptomic Analyses of Rigid and Membranous Cuticles and Epidermis from the Elytra and Hindwings of the Red Flour Beetle, Tribolium castaneum

Abstract: The insect cuticle is a composite biomaterial made up primarily of chitin and proteins. The physical properties of the cuticle can vary greatly from hard and rigid to soft and flexible. Understanding how different cuticle types are assembled can aid in the development of novel biomimetic materials for use in medicine and technology. Toward this goal, we have taken a combined proteomics and transcriptomics approach with the red flour beetle, Tribolium castaneum, to examine the protein and gene expression profil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
68
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 78 publications
(73 citation statements)
references
References 59 publications
2
68
0
Order By: Relevance
“…Bioinformatics searches of fully sequenced and annotated genomes of several insect species such as the honey bee, Apis melifera (Honeybee Genome Sequencing Consortium, 2006), the fruit fly, Drosophila melanogaster (Karouzou et al, 2007) and the red flour beetle, Tribolium castaneum (Dittmer et al, 2012;Richards et al, 2008) indicate that there is a large number of genes encoding CP-like proteins in insect genomes. Indeed, more than 200 putative CP genes have been identified in the malaria mosquito, Anopheles gambiae (Cornman et al, 2008) and the silkworm, Bombyx mori (Futahashi et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bioinformatics searches of fully sequenced and annotated genomes of several insect species such as the honey bee, Apis melifera (Honeybee Genome Sequencing Consortium, 2006), the fruit fly, Drosophila melanogaster (Karouzou et al, 2007) and the red flour beetle, Tribolium castaneum (Dittmer et al, 2012;Richards et al, 2008) indicate that there is a large number of genes encoding CP-like proteins in insect genomes. Indeed, more than 200 putative CP genes have been identified in the malaria mosquito, Anopheles gambiae (Cornman et al, 2008) and the silkworm, Bombyx mori (Futahashi et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, more than 200 putative CP genes have been identified in the malaria mosquito, Anopheles gambiae (Cornman et al, 2008) and the silkworm, Bombyx mori (Futahashi et al, 2008). T. castaneum has 108 genes encoding CP-like proteins (Dittmer et al, 2012;Richards et al, 2008). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[8][9][10][11] Our research team recently identified and sequenced several abundant proteins within the elytron (rigid forewing) of Tribolium castaneum. [12] The third most abundant protein in the elytron is CP30 (or GLEAN no. 14462).…”
Section: Introductionmentioning
confidence: 99%
“…14462). [12] CP stands for cuticle protein and 30 reflects the fact that it tracks with the 30 kDa standard protein in SDS-PAGE. It has a molar mass of 19 kDa with an isoelectric point of pH 5.82.…”
Section: Introductionmentioning
confidence: 99%